“Healthcare professionals’ attitudes towards euthanasia in the Balearic Islands.” - Daniel Lerma-García; Juan Carlos Muñoz-Camargo; Laura Cervantes-Torres; Sandra Martínez-Rodríguez; María Dolores Onieva-Zafra (BMC Medical Ethics)
Abstract Background Euthanasia is a topic of ethical, legal, and medical debate, particularly among healthcare professionals, who play a key role in its implementation. Their attitudes toward euthanasia are essential for shaping healthcare policies and training programs, as these professionals must navigate complex moral and practical considerations in their daily practice. Understanding these perspectives is key to ensuring appropriate policy development and providing effective education for healthcare providers. Objective This study aims to analyze the sociodemographic factors influencing attitudes toward euthanasia among healthcare professionals in the Balearic Islands and examine the correlation between two scales measuring these attitudes. Methods A cross-sectional study was conducted with a sample of 746 healthcare professionals from the Balearic Health Service. Participants completed a validated questionnaire assessing their attitudes toward euthanasia with the Euthanasia Attitude Scale and the Attitude Toward Euthanasia, along with a socio-demographic questionnaire. Results The findings reveal that attitudes toward euthanasia are significantly influenced by variables such as age, gender, religious beliefs, and professional experience. Younger professionals, males, and those with fewer religious convictions tend to express more favorable attitudes toward euthanasia. Differences were also observed across professional categories, with nurses generally showing greater acceptance compared to physicians and other healthcare workers. Conclusion Sociodemographic factors play a crucial role in shaping healthcare professionals’ attitudes toward euthanasia. These findings underscore the importance of tailored educational strategies and policy considerations to address diverse perspectives within the healthcare sector.